2004
DOI: 10.1124/jpet.104.073965
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Specific Amyloid-β(1-42) Suppression by Nonsteroidal Anti-Inflammatory Drugs in Young, Plaque-Free Tg2576 Mice and in Guinea Pig Neuronal Cultures

Abstract: Recent studies indicating that some nonsteroidal anti-inflammatory drugs (NSAIDs) selectively modulate gamma-secretase cleavage of amyloid precursor protein (APP) while sparing Notch processing have generated interest in discovery of novel gamma-secretase modulators with the "NSAID-like" efficacy profile. The objective of the present studies was to compare the efficacy of a subset of NSAIDs with previously reported classical gamma-secretase inhibitors LY-411575 [N(2)-[(2S)-2-(3,5-difluorophenyl)-2-hydroxyethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 28 publications
5
48
0
Order By: Relevance
“…These brain concentrations are not higher than those attained in young transgenic Tg2576 mice after short-term treatment (10.2 Ϯ 3.7 M, after 100 mg/kg/day for 4 days) where we failed to demonstrate a decrease in brain A␤ levels (Imbimbo et al, 2007). This is in line with previous reports indicating that short-term administration (3-8 days) of A␤-lowering NSAIDs in young Tg2576 transgenic mice does not attain significant effects on brain A␤ levels (Lanz et al, 2005;Peretto et al, 2005;Stock et al, 2006). Alternatively, long-term treatments (3-8 months) with ibuprofen (Lim et al, 2000(Lim et al, , 2001Yan et al, 2003) indomethacin (Sung et al, 2004), or flurbiprofen derivatives (Jantzen et al, 2002;van Groen et al, 2005;Wilcock et al, 2007) have shown a significant reduction in brain A␤ pathology in transgenic mice.…”
Section: Discussionsupporting
confidence: 92%
“…These brain concentrations are not higher than those attained in young transgenic Tg2576 mice after short-term treatment (10.2 Ϯ 3.7 M, after 100 mg/kg/day for 4 days) where we failed to demonstrate a decrease in brain A␤ levels (Imbimbo et al, 2007). This is in line with previous reports indicating that short-term administration (3-8 days) of A␤-lowering NSAIDs in young Tg2576 transgenic mice does not attain significant effects on brain A␤ levels (Lanz et al, 2005;Peretto et al, 2005;Stock et al, 2006). Alternatively, long-term treatments (3-8 months) with ibuprofen (Lim et al, 2000(Lim et al, , 2001Yan et al, 2003) indomethacin (Sung et al, 2004), or flurbiprofen derivatives (Jantzen et al, 2002;van Groen et al, 2005;Wilcock et al, 2007) have shown a significant reduction in brain A␤ pathology in transgenic mice.…”
Section: Discussionsupporting
confidence: 92%
“…Weggen et al (2001) demonstrated that selective NSAIDs induce alteration of the ␥-secretase cleavage pattern, which leads to reduced production of A␤42, without affecting A␤40 levels. Selective reduction of A␤42 was also seen in our study but not in some other studies where non-indomethacin, ␥-secretase inhibitors were employed (Lanz et al, 2005). We used the same model and dosing paradigm (high doses for a very short period) reported by Weggen et al (2001) since it resulted in consistent reduction in A␤42.…”
Section: Dp-155 Safer Indomethacin Reducing A␤ 1-42 1253supporting
confidence: 59%
“…Third, NSAIDs may have off-target effects. Some studies have demonstrated that an acute, relatively shortterm administration of selected NSAIDs to AD mouse models results in decreased production of longer Aβ peptides, in favor of shorter, less-amyloidogenic isoforms (56), although not all studies have observed this effect (57). This would offer a potential nonimmune mechanism of NSAID action.…”
Section: Discussionmentioning
confidence: 99%